Odpowiedź :
Odpowiedź:
a)
1/3x - 2 = x + 2 | * 3
x - 6 = 3x+ 6
x - 3x = 6 + 6
- 2x = 12
2x = -12
x = -12/2 = - 6
b)
1 - 6/7x = 4/7 | * 7
7 - 6x = 4
- 6x = 4 - 7
- 6x = - 3
6x = 3
x = 3/6 = 1/2
c)
6(1/4x - 2 ) = 18
6/4x - 12 = 18 | * 4
6x - 48 = 72
6x= 72+ 48 = 120
x = 120/6 = 20
d)
x/6 - 1/6 = 1 | * 6
x - 1 = 6
x= 6 + 1 = 7
e)
-2(2x - 1) = x/3 | * 3
- 6(2x - 1) = x
- 12x + 6 = x
- 12x - x = - 6
- 13x = - 6
13x = 6
x = 6/13
f)
2/5(3 - x) = - 2 | * 5
2(3 - x) = - 10
6 - 2x = - 10
- 2x = - 10 - 6
- 2x = - 16
2x = 16
x = 16/2 = 8
g)
3/4(2 - 3x) = - 6 | * 4
3(2 - 3x) = - 24
6 - 9x = - 24
- 9x = - 24 - 6
- 9x = - 30
9x = 30
x = 30/9 = 10/3 = 3 1/3
h)
1/5(x - 3) = 9 - x | * 5
x - 3 = 5(9 - x)
x - 3 = 45 - 5x
x + 5x = 45 + 3
6x = 48
x = 48/6 = 8
i)
(0,6 + x)/2 = x + 1 | * 2
0,6 + x = 2(x + 1)
0,6 + x = 2x + 2
x - 2x = 2 - 0,6
- x = 1,4
x = - 1,4
a)
[tex]\frac{1}{3}x-2=x+2\\ \frac{1}{3}x-x=2+2\\-\frac{2}{3}x=4/:(-\frac{2}{3})\\x=4*(-\frac{3}{2})\\x=-6[/tex]
b)
[tex]1-\frac{6}{7}x=\frac{4}{7}\\-\frac{6}{7}x=\frac{4}{7}-1\\-\frac{6}{7}x=-\frac{3}{7}/:(-\frac{6}{7})\\x=(-\frac{3}{7})*(-\frac{7}{6})\\x=\frac{1}{2}[/tex]
c)
[tex]6(\frac{1}{4}x-2)=18\\\frac{3}{2}x-12=18\\\frac{3}{2}x=18+12\\\frac{3}{2}x=30/:\frac{3}{2}\\x=30*\frac{2}{3}\\x=20[/tex]
d)
[tex]\frac{x}{6}-\frac{1}{6}=1/*6\\x-1=6\\x=6+1\\x=7[/tex]
e)
[tex]-2(2x-1)=\frac{x}{3}/*3\\-6(2x-1)=x\\-12x+6=x\\-12x-x=-6\\-13x=-6/:(-13)\\x=\frac{6}{13}[/tex]
f)
[tex]\frac{2}{5}(3-x)=-2/*5\\2(3-x)=-10\\6-2x=-10\\-2x=-10-6\\-2x=-16/:(-2)\\x=8[/tex]
g)
[tex]\frac{3}{4}(2-3x)=-6/*4\\3(2-3x)=-24\\6-9x=-24\\-9x=-24-6\\-9x=-30/:(-9)\\x=\frac{10}{3}=3\frac{1}{3}[/tex]
h)
[tex]\frac{1}{5}(x-3)=9-x /*5\\x-3=45-5x\\x+5x=45+3\\6x=48/:6\\x=8[/tex]
i)
[tex]\frac{0,6+x}{2}=x+1/*2\\0,6+x=2x+2\\x-2x=2-0,6\\-x=1,4/:(-1)\\x=-1,4[/tex]